2008
DOI: 10.1073/pnas.0801496105
|View full text |Cite
|
Sign up to set email alerts
|

ESAT-6-specific CD4 T cell responses to aerosolMycobacterium tuberculosisinfection are initiated in the mediastinal lymph nodes

Abstract: CD4 ؉ T cell responses to aerosol Mycobacterium tuberculosis (Mtb) infection are characterized by the relatively delayed appearance of effector T cells in the lungs. This delay in the adaptive response is likely critical in allowing the bacteria to establish persistent infection. Because of limitations associated with the detection of low frequencies of naïve T cells, it had not been possible to precisely determine when and where naïve antigen-specific T cells are first activated. We have addressed this proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
215
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 204 publications
(225 citation statements)
references
References 30 publications
9
215
1
Order By: Relevance
“…and in LTbR-and LTbRxSp-deficient mice by days 38 and 45, respectively (Fig 5C and D). Because CD69 is rapidly down-regulated upon egress from LN and was restricted to mediastinal LN T cells early during MTB infection, these data suggest that T cells may be primed locally in lungs at later stages of infection in WT and LTbR-deficient mice [22].…”
Section: Normal T-cell Development Without Slomentioning
confidence: 89%
See 1 more Smart Citation
“…and in LTbR-and LTbRxSp-deficient mice by days 38 and 45, respectively (Fig 5C and D). Because CD69 is rapidly down-regulated upon egress from LN and was restricted to mediastinal LN T cells early during MTB infection, these data suggest that T cells may be primed locally in lungs at later stages of infection in WT and LTbR-deficient mice [22].…”
Section: Normal T-cell Development Without Slomentioning
confidence: 89%
“…and in LTbR-and LTbRxSp-deficient mice by days 38 and 45, respectively (Fig 5C and D). Because CD69 is rapidly down-regulated upon egress from LN and was restricted to mediastinal LN T cells early during MTB infection, these data suggest that T cells may be primed locally in lungs at later stages of infection in WT and LTbR-deficient mice [22]. To verify whether T-cell priming outside of SLO induced a complete effector T-cell developmental program, we examined expression of CD27, a surface marker which is down-regulated on terminally differentiated effector T cells.…”
Section: Normal T-cell Development Without Slomentioning
confidence: 89%
“…Immune response to MTB infection is primarily mediated by T cells (Lockhart et al 2006). In previous research of human pulmonary TB, T cells responding to ESAT-6 are observed in approximately half of the patients (Guinn et al 2004;Reiley et al 2008). ESAT-6, a vital immune-dominant antigen encoded by region of difference-1 (RD1) and RD2, has been reported to have the potential for human MTB diagnosis (Sang and Zhang 2012;Li et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocytes isolated from infected mice were incubated in a 96-well plate, at a concentration of 3 × 10 6 cells per well. Cells were incubated in the presence of ESAT-6 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] or Sendai HN [421][422][423][424][425][426][427][428][429][430][431][432][433][434][435][436] peptide (5 μg/mL each) for 2 h at 37°C; Brefeldin A (50 μg/mL) was added, and the incubation was continued for an additional 4 h. Surface staining for CD4, CD8, PD-1, and KLRG1 was performed, as described previously (22), and the cells were fixed and permeabilized using a Cytofix/Cytoperm Fixation/ Permeabilization kit (BD Biosciences). For detection of intracellular IFNγ and TNFα, the cells were incubated for 30 min in Perm/Wash Buffer (BD Biosciences) with anti-IFNγ (clone XMG1.2) and anti-TNFα (clone MP6-XT22); the cells were analyzed as described above.…”
Section: Methodsmentioning
confidence: 99%